2017
DOI: 10.1128/aac.02627-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Bedaquiline against Nontuberculous Mycobacteria in China

Abstract: The main goal of our study was to evaluate the in vitro bedaquiline susceptibility of six prevalent species of pathogenic nontuberculous mycobacteria (NTM) in China. In addition, we investigated the potential molecular mechanisms contributing to bedaquiline resistance in the different NTM species. Among slowly growing mycobacteria (SGM), bedaquiline exhibited the highest activity against 44 (20.2%), 42 (25.8%), and 7 (31.8%), respectively, were resistant to bedaquiline. No significant differences in the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
70
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 27 publications
9
70
2
3
Order By: Relevance
“…Bdq also exhibited very good inhibitory activities against most of the tested clinical SGM isolates, especially the most prevalent and highly pathogenic species, such as M. kansasii and Mycobacterium avium complex (MAC), as previously described (10). Pang et al also demonstrated that Bdq had good inhibitory activities against clinical strains of some SGM species isolated from China (9). All the tested NTM isolates in this study were collected in four hospitals located in mideastern China from 2011 to 2015, while the NTM isolates in our study were collected in Beijing Chest Hospital located in northern China from 2015 to 2016.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Bdq also exhibited very good inhibitory activities against most of the tested clinical SGM isolates, especially the most prevalent and highly pathogenic species, such as M. kansasii and Mycobacterium avium complex (MAC), as previously described (10). Pang et al also demonstrated that Bdq had good inhibitory activities against clinical strains of some SGM species isolated from China (9). All the tested NTM isolates in this study were collected in four hospitals located in mideastern China from 2011 to 2015, while the NTM isolates in our study were collected in Beijing Chest Hospital located in northern China from 2015 to 2016.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, we also evaluated the activity of Bdq and Dlm against 52 reference strains of different mycobacterium species to gain insights on their potential use for specific NTM species. As they are new drugs, well-recognized susceptibility testing methods for Bdq and Dlm have not been developed, and breakpoints to define drug resistance for them have never been discussed prudently (9,10). Defining the ECOFF value based on data produced by multiple centers with a large number of strains is an important step to establish the breakpoints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diseases due to nontuberculous mycobacteria are similar to those due to MDR-TB in that there are few treatment options available, especially for patients with M. avium complex and M. abscessus (24). More importantly, relatively less effort has been devoted to new drug discovery and development.…”
mentioning
confidence: 99%